1973
DOI: 10.1002/food.19730170311
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Composition of Cereal and Oilseed

Abstract: Quantitative amino acid composition of acid hydrolysates was determined for samples of some Polish varieties of cereal grain (wheat, rye, barley, oats, millet and buckwheat) and oilseed (rapeseed, sunflower, poppy and soybean). Comparison of investigated genera was done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Renz (1970) has reported that [14C]riboflavin is an efficient precursor of the DBI moiety of vitamin Bi2 in broken cell preparations of P. shermanii. It has also been established that P. shermanii cultures produce riboflavin (Janicki et al, 1966). The labeling results reported here, as well as earlier labeling results from the 6,7-[14C]dimethyl-8-ribityllumazine precursor, are consistent with two reasonable biosynthetic pathways.…”
Section: Resultssupporting
confidence: 88%
“…Renz (1970) has reported that [14C]riboflavin is an efficient precursor of the DBI moiety of vitamin Bi2 in broken cell preparations of P. shermanii. It has also been established that P. shermanii cultures produce riboflavin (Janicki et al, 1966). The labeling results reported here, as well as earlier labeling results from the 6,7-[14C]dimethyl-8-ribityllumazine precursor, are consistent with two reasonable biosynthetic pathways.…”
Section: Resultssupporting
confidence: 88%